1995
DOI: 10.1002/pola.1995.080330411
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonate synthesis by the melt phase carbonate‐ester interchange reaction of bisphenol‐A diacetate with dimethyl carbonate

Abstract: The molecular weight of polycarbonate formed by the carbonate‐ester interchange reaction of bisphenol‐A diacetate (BPAC2) and dimethyl carbonate (DMC) was found to depend on the composition of the oligomer formed in its first stage. At a [DMC] : [BPAC2] ratio of 2, an oligomer with relatively higher acetate end group concentration was formed. This upon further polycondensation yielded a polycarbonate of inherent viscosity, 0.2‐0.25 dL/g. Upon addition of DMC at a later stage in the oligomer‐forming reaction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The bulky amorphous chains produce considerable free volume, which results in high ductility and impact resistance 6. The combination of all these characteristics leads to properties such as high optical clarity, percent elongation, impact strength, toughness, heat resistance, and heat deflection temperature 14–16. Uses of BPAPC is spread in many areas, which include construction, electrical, automotive, aircraft, marine, medical (pumps, connectors, fluid administration applications like stopcocks, catheters, syringes, blood oxygenetaors, and kidney dialyzers), and packaging.…”
Section: Introductionmentioning
confidence: 99%
“…The bulky amorphous chains produce considerable free volume, which results in high ductility and impact resistance 6. The combination of all these characteristics leads to properties such as high optical clarity, percent elongation, impact strength, toughness, heat resistance, and heat deflection temperature 14–16. Uses of BPAPC is spread in many areas, which include construction, electrical, automotive, aircraft, marine, medical (pumps, connectors, fluid administration applications like stopcocks, catheters, syringes, blood oxygenetaors, and kidney dialyzers), and packaging.…”
Section: Introductionmentioning
confidence: 99%
“…Phosgene is also a corrosive and expensive substance, and the method produces wasted sodium chloride contaminated with organic substances 6. Because there is increasing pressure to avoid the use of chlorinated organic solvents in the chemical industry, the search for a safer and an environmentally benign processing route to PC that does not involve phosgene and chlorinated solvents is required 5, 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…Deshpande et al 27 also reported that the higher content of carbonate-ended oligomer led to the higher molecular weight of the polymer in the reaction of BPA diacetate with DMC. 27,28 It was proposed to replace BPA with BPA diacetate or 1,4-bis(hydroxymethyl) cyclohexane 26 because of the low activity of the transesterification of BPA and DMC.…”
Section: Introductionmentioning
confidence: 94%
“…[25][26][27][28][29] Shaikh et al 25 and Haba et al 29 reported that the methylcarbonate-ended oligomers from the transesterification of BPA and DMC were most reactive in producing high molecular weight polymers in the postpolycondensation step compared with hydroxyl-ended oligomers. Deshpande et al 27 also reported that the higher content of carbonate-ended oligomer led to the higher molecular weight of the polymer in the reaction of BPA diacetate with DMC. 27,28 It was proposed to replace BPA with BPA diacetate or 1,4-bis(hydroxymethyl) cyclohexane 26 because of the low activity of the transesterification of BPA and DMC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation